The Impact of L'Oréal Paris Fall Repair‘s Celebrity Endorsement towards Consumer Purchase Intention with Brand Image as a Mediating Variable - Anastasia Andrea Widjaja (iBuss Management, 2015)
Hair fall problem had been in the second rank for the most common hair problems faced by women in Indonesia since 2010 to 2014. Hence, L'Oréal Paris Fall Repair that was just launched in 2013 has had potential chance to fulfill market need. However, L'Oréal Paris Fall Repair needs to compete with other famous hair fall brands. Therefore, this research is conducted to help analyzing the current L'Oréal Paris Fall Repair’s celebrity endorsement is. The primary data of this research comes from 117 filled questionnaires. Afterwards, path analysis is used to identify the relationship of independent, mediating, and dependent variable. The result indicates that there is significant positive impact of L'Oréal Paris Fall Repair’s celebrity endorsement towards consumer purchase intention with brand image as a mediating variable.Keywords: Celebrity Endorsement, Brand Image, Consumer Purchase Intention, Path Analysis